1https://edu.gounn.ru/journal-api-online_lessons-action?action=setStudentDateStart&isExtDay=0&onlineLessonId=48https://edu.gounn.ru/journal-api-online_lessons-action?action=setStudentDateStart&isExtDay=0&onlineLessonId=48https://edu.gounn.ru/journal-api-online_lessons-action?action=setStudentDateStart&isExtDay=0&onlineLessonId=48https://edu.gounn.ru/journal-api-online_lessons-action?action=setStudentDateStart&isExtDay=0&onlineLessonId=48https://edu.gounn.ru/journal-api-online_lessons-action?action=setStudentDateStart&isExtDay=0&onlineLessonId=48https://edu.gounn.ru/journal-api-online_lessons-action?action=setStudentDateStart&isExtDay=0&onlineLessonId=48
=-2(cosπ/3cos2a+sinπ/3sin2a)+6=-2(1/2*cos2a+√3/2sin2a)+6=
=-cos2a-√3sin2a+6